Analgesic effects of intra-articular ropivacaine following arthroscopic knee surgery: Results of a double-blind, randomized controlled trial between two different doses - Hazra, Rajdip; Manuar, Md. Babrak; Manjunatha, SM; Chakraborty, Sisir; Ghosh, Kaushik; Basu, Rajarshi; Nurejjaman, Md.; Kumar, Arun N; Yathish, SK (Asian Journal of Medical Sciences, 2014)
Background: Though local anesthetic agents are widely used to provide postoperative analgesia in intra-articular route, their efficacy is not accepted universally. Objective: The present study has been conducted to compare the analgesic effects of intra-articular ropivacaine between two different doses following arthroscopic knee surgery. Study design: Double-blinded randomized controlled trial. Total 60 patients of ASA (American Society of Anesthesiologists) physical status I and II, 34 male and 26 female, aged between 18 to 60 years, were randomized into 3 groups receiving 10 ml normal saline, 10 ml 0.5% ropivacaine and 10 ml 0.75% ropivacaine respectively, administered in intra-articular space at the end of operation. Results: Ropivacaine groups had significantly delayed first post-operative rescue analgesic request with significantly lesser requirement of rescue analgesia in first 24 hours (p<0.001 in both cases). Except 6th post-operative hours, ropivacaine groups also showed significantly less VAS scores (Visual Analogue Scale) up to 12 hours post-operatively (p<0.05). Conclusion: In our double-blinded randomized controlled trial, administration of intra-articular 0.75% ropivacaine showed superior analgesic efficacy following arthroscopic knee surgery. Further, larger trials are needed to confirm our findings. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9703 Asian Journal of Medical Sciences Vol.6(1) 2015 81-86